Time Trends of Allergic Rhinitis and Effects of Residence on Allergic Rhinitis in Korea From 1998 Through 2007-2009 - Jun-Pyo Myong, MD, MPH; Hyeongsu Kim, MD, PhD; Kunsei Lee, MD, PhD; Sounghoon Chang, MD, PhD (Elsevier, 2012)
Purpose: Longitudinal changes in the prevalence of self-reported physician-diagnosed allergic rhinitis (AR) in Korea and the association between the prevalence of AR and type of residence area among Korean males and females in 1998, 2001, 2005 and 2007-2009 were evaluated. Methods: Age-standardized prevalence was calculated using the Korea National Health and Nutrition Examination Survey (KNHANES) I-IV. Stratified factors of sex, age, and socioeconomic status were adjusted to compare the prevalence of AR in relation to residential area by multiple logistic analysis. Results: The prevalence of AR increased by tenfolds from 1.2 % in 1998 to 12.0 % in 2007-2009. The trends for prevalence of AR were also statistically significant (p < .05). The age-standardized prevalence of AR among urban females was higher (13.9%) than that in rural females (11.5%). After adjustment for survey years, age, socioeconomic levels and asthma, the odds of AR were higher in urban than rural residents, except for males in 1998. Conclusion: The prevalence of AR in Korea has increased over the past decade, and living in an urban area may be a susceptible factor. For prevention and management of AR, further evaluations of contributing factors and mechanisms underlying differences in AR are needed.